Endocrinology delivery - Coyotupa Vegas, Juan (2015)
The endocrine control of starting and maintaining the delivery is not fully explained in women. In an attempt to understand the mechanism involved in childbirth, it is reviewed not only the effects in humans, but also extrapolated experiments in animals that allow us to better understand the process.